2002
DOI: 10.1136/bjo.86.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Blinking and operating: cognition versus vision

Abstract: ReferencesIf you have a burning desire to respond to a paper published in the BJO, why not make use of our "rapid response" option? Log on to our website (www.bjophthalmol.com), find the paper that interests you, and send your response via email by clicking on the "eLetters" option in the box at the top right hand corner.Providing it isn't libellous or obscene, it will be posted within seven days. You can retrieve it by clicking on "read eLetters" on our homepage.The editors will decide as before whether to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…One explanation for the higher prevalence of dry eye symptoms when viewing screens may be due to changes in blink patterns. Several investigations have reported that the blink rate is reduced during computer operation (Patel, Henderson, Bradley, Galloway, & Hunter, 1991;Schlote, Kadner, & Freudenthaler, 2004;Tsubota & Nakamori, 1993;Wong, Wan, & Kaye, 2002). For example, Tsubota and Nakamori (1993) compared the rate of blinking in 104 office workers either when they were relaxed, reading a book or viewing text on an electronic screen.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for the higher prevalence of dry eye symptoms when viewing screens may be due to changes in blink patterns. Several investigations have reported that the blink rate is reduced during computer operation (Patel, Henderson, Bradley, Galloway, & Hunter, 1991;Schlote, Kadner, & Freudenthaler, 2004;Tsubota & Nakamori, 1993;Wong, Wan, & Kaye, 2002). For example, Tsubota and Nakamori (1993) compared the rate of blinking in 104 office workers either when they were relaxed, reading a book or viewing text on an electronic screen.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it is well known that eyeblink rate is affected by performing tasks that require attention. Wong and colleagues, for instance, noted that the rate in ophthalmologic surgeons decreased during the execution of surgery, from 16 to 4 eyeblinks per minute [ 13 ]. The connection between eyeblink and attention has been proven in various circumstances [ 14 ] including the use of screens [ 15 , 16 ], or for diagnosis in Autism Spectrum Disorders [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, here we found that this happens with a clearer impact on media professionals, suggesting that this group is more sensitive to cuts. The rate of blinking has been proven to decrease when a cognitive operation is performed (Holland and Tarlow, 1975 ; Wong et al, 2002 ). Some studies have shown that watching a film reduces viewers' eyeblink rate (Patel et al, 1991 ; Andreu-Sánchez et al, 2017a ), and it has been proposed that this decrease may be a strategy to minimize the loss of visual information (Nakano et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%